Artikel PENERAPAN NILAI – NILAI KARARTER MELAULUI PROGRAM EXTRAKURIKULER PASKIBRA PADA PESERTA DIDIK KELAS VI DI SDK MUNTA KECAMATAN MACANG PACAR KABAUPATEN MANGGARAI BARAT - Jehartu, Inovensius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research objectives are as follows: 1. To find out the application of character values ?carried out by the school through the Paskibra extracurricular program for grade VI students at SDK Munta, Macang girlfriend subdistrict. 2. To find out about the implementation of Paskibra extracurricular activities at SDK Munta, Macang girlfriend district? The type of research used in this research is qualitative. This research is research that uses a qualitative descriptive approach The research subjects were the school principal, Paskibra supervisor, and class VI students. Data collection techniques: Interviews, Observations, and Documentation. The results of the research show that: 1. In the activity process, the prioritized character values, namely religious, discipline, responsibility, honesty, have been implemented by the paskibra coaches through activities such as Barisan activities, direction, advice, habituation, which are carried out indirectly. will directly shape the character of students. 2. The aim of extracurricular activities is to educate students or Paskibra members to become a generation with character in accordance with the goals of Paskibra. At SDK Munta, this activity is carried out regularly every week. Keywords: Formulation, , Physical Education Efforts to develop and increase a person's knowledge carried out by people or organizations (schools or universities) are called education. So, to guide, develop and shape students so that they are in line with Indonesia's educational goals, this can be done by implementing character education in each institution. Extracurricular activities are enrichment activities and improvement activities related to curricular programs Extracurricular activities are educational activities outside class.